Determinación del costo del servicio por procedimientos quirúrgicos seleccionados bajo la metodología ABC en la clínica oftalmológica de Palmira (2021)
The Activity Based Costing system, also known as ABC costing, is a costing system used to identify, recognize and value the activities that generate value within the execution process of the economic activity developed by the company, also controlling the use of resources in each of the tasks.